2009
DOI: 10.1007/s12020-009-9229-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosiglitazone on ovarian function and fertility in animals with reduced fertility following fetal and neonatal exposure to nicotine

Abstract: We have previously shown that in utero nicotine exposure causes impaired fertility, follicle immaturity, and ovarian dysfunction in adult female rat offspring. These characteristics overtly resemble the clinical profile of polycystic ovarian syndrome (PCOS) and recent studies have shown that thiazolidinediones such as rosiglitazone improve fertility in women with PCOS but the mechanism is not well defined. Our goal was to examine whether rosiglitazone would (1) ameliorate the altered ovarian physiology that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
3
31
0
1
Order By: Relevance
“…Interestingly, it has been reported that PPAR␥ activation by rosiglitazone reversed adverse nicotine effects on the ovary vascularization by increasing EG-VEGF expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that PPAR␥ activation by rosiglitazone reversed adverse nicotine effects on the ovary vascularization by increasing EG-VEGF expression (37).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no human studies examining the reproductive outcomes in children exposed to NRTs in utero. Studies in animal models have identified that prenatal exposure to nicotine alone can result in increased germ cell depletion and altered steroidogenesis in male offspring (Lagunov et al 2011, Paccola et al 2014) and increased ovarian cell apoptosis, altered steroidogenesis, and impaired fertility in female offspring (Holloway et al 2006, Petrik et al 2009.…”
Section: Postnatal Health Outcomesmentioning
confidence: 99%
“…The relationship between nicotine, oxidative stress, and ovarian physiology has been less well studied, although nicotine has been shown to cause oxidative stress in Chinese Hamster Ovary cells (Yildiz et al 1998, Yildiz 2004. Importantly, oxidative stress is associated with increased ovarian cell apoptosis and follicle loss -outcomes that have been similarly observed in rats exposed to nicotine in adulthood (Camargo et al 2014) and fetal life (Petrik et al 2009). Collectively, these findings suggest that nicotine-induced oxidative stress may be an important, and potentially modifiable, pathway leading to impaired reproductive health in the offspring.…”
Section: Cellular Mechanisms Underlying Adverse Nicotine-induced Reprmentioning
confidence: 99%
See 2 more Smart Citations